Effects of wooden-dowel species, edge banding thickness, and adhesive types on withdrawal strength in MDF-Lam. Issue 4 (4th July 2021) - Karaman, Abdurrahman
ABSTRACT: Composite materials, edge banding, and wooden dowels are being used in inner decoration and the construction of furniture frames. However, there is little information available concerning the withdrawal strength of various fasteners and in particular, dowels in these materials. The aim of this study was to determine the withdrawal strengths of PVC edge bandings with 0.8, 1, and 2 mm thicknesses, and dowels produced from six different wood species bonded parallel to the surfaces of a melamine coated medium density fiberboard (MDF-Lam) with polyvinyl acetate (PVAc-D4) or polyurethane (PU-D4). According to TS 4539 standard, the effect of wooden dowel species, thickness of edge banding, and the type of adhesives on the withdrawal strength were determined. Withdrawal strength values of polyurethane (PU-D4) were found 65% higher than the withdrawal strength values of polyvinyl acetate (PVAc-D4). The highest (8.35 N/mm 2 ) withdrawal strength was obtained for oak dowels bonded with polyurethane (PU-D4) adhesive vertical to the surface of MDF-Lam. The lowest withdrawal strength value was obtained from the dowel produced from oak with polyvinyl acetate (PVAc-D4) adhesive in the samples without PVC edge banding. This value is higher than the predictive statement that allows designers to estimate the withdrawal strength of dowels.